Occurrence of bovine tuberculosis among cattle herds from nomadic peri-urban settlements and cattle slaughtered at the municipal abattoir of Bauchi, North-Eastern Nigeria - Jajere, Saleh Mohammed; Atsanda, Naphtali Nayamanda; Bitrus, Asinamai Athliamai; Hamisu, Tasiu Mallam; Goni, Mohammed Dauda (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was designed to determine the prevalence of bovine tuberculosis (bTB) at the municipal abattoir and cattle herds in peri-urban nomadic settlements of Bauchi state of Northeastern Nigeria. Materials and Methods: A total of 2440 cattle slaughtered at the municipal abattoir from June to September were examined for lesions characteristic of bTB and eighty-six (n=86) cows selected from two cattle herds located at temporary nomadic settlements in Bauchi metropolis were also screened for bTB using purified protein derivative (PPD) tuberculin skin test. During the study period, total of 2,440 cattle were slaughtered comprising majority of females (n=1656) and males (n=784) as well as of different breeds including majority of White Fulani (n=1864) followed by Red Bororo (n=508) and Sokoto Gudali (n=68). Results: The results revealed that out of the 2,440 slaughtered cattle inspected for tuberculous-like lesions, 51 had lesions suspected to be lesions characteristic of tuberculosis, while 48 were positive for Ziehl-Neelsen. Prevalence rate of 1.96% based on microscopic examination and 2.0% based on suspected gross lesion were recorded. The prevalence was 0.77% for males, 1.2% females, 1.84% for adults, 0.12% for calves and 1.8% for white Fulani (Bunaji), 0.12% for Red Bororo (Rahaji) and 0.04% for Sokoto Gudali (Bokoloji). In addition, screening of 86 cows showed that 8.1% were positive for tuberculosis using tuberculin test. Conclusion: The outcome of this study showed that bTB is still endemic in Bauchi state and this can pose a significant public health challenge. Thus, it is recommended that the government should intensify the test-and-slaughter policy as well as put in place an effective monitoring and surveillance control programs for bTB to mitigate the risks posed to public health by this zoonotic disease in the study area. http://doi.org/10.5455/javar.2018.e247